Aerobic C–H Functionalization Using Pyrenedione as the Photocatalyst - Zhang, Yuannian; Yang, Xin; Wu, Jie; Huang, Dejiang (Synthesis, 2020)
We disclose a visible-light-promoted aerobic alkylation of activated C(sp3)–H bonds using pyrenedione (PYD) as the photocatalyst. Direct C–H bond alkylation of tetrahydrofuran with alkylidenemalononitriles is accomplished in over 90% yield in the presence of 5 mol% of PYD and 18 W blue LED light under ambient conditions. The substrate scope is extended to ethers, thioethers, and allylic C–H bonds in reactions with various electrophilic Michael acceptors. The catalytic turnover process is facilitated by oxygen. Our work represents the first example of using PYD as a photocatalyst to promote C(sp3)–H alkylation, revealing the unique character of PYD as a novel organophotocatalyst.
Keywords: organophotocatalysts; pyrenedione; alkylation; tetrahydrofuran; visible light